Achieving ‘step changes’ in science and innovation: Towards ‘Pasteur’s paddock’? - Baisden, Troy (New Zealand Science Review, 2014)
​The Request for Proposals for New Zealand’s National Science Challenges (NSCs) emphasises that successful proposals should ‘represent a significant step change in undertaking research and delivering impact’ (MBIE 2014). How can a ‘step change’ be achieved within NSCs where new funding is small compared to realigned funding? In a video released on 4 February 2014, the Minister for Science and Innovation suggests an expectation that ‘additionality’ will play a key role, with ‘collaborative’ and ‘multidisciplinary’ endeavour as important compo-nents of these ‘mission-led’ Challenges (Joyce 2014). This brief communication reviews and describes a timely synthesis of two important components of the science and innovation literature relevant to the ‘step change’ and ‘additionality’ expectations in NSCs.